Seasonal evolution of Saturn's polar temperatures and composition - Fletcher, L; Irwin, P; Sinclair, J; Orton, G; Giles, R; Hurley, J; Gorius, N; Achterberg, R; Hesman, B; Bjoraker, G (Academic Press Inc., 2015)
The seasonal evolution of Saturn's polar atmospheric temperatures and hydrocarbon composition is derived from a decade of Cassini Composite Infrared Spectrometer (CIRS) 7-16μm thermal infrared spectroscopy. We construct a near-continuous record of atmospheric variability poleward of 60° from northern winter/southern summer (2004, Ls=293°) through the equinox (2009, Ls=0°) to northern spring/southern autumn (2014, Ls=56°). The hot tropospheric polar cyclones that are entrained by prograde jets within 2-3° of each pole, and the hexagonal shape of the north polar belt, are both persistent features throughout the decade of observations. The hexagon vertices rotated westward by ≈30° longitude between March 2007 and April 2013, confirming that they are not stationary in the Voyager-defined System III longitude system as previously thought. Tropospheric temperature contrasts between the cool polar zones (near 80-85°) and warm polar belts (near 75-80°) have varied in both hemispheres, resulting in changes to the vertical windshear on the zonal jets in the upper troposphere and lower stratosphere. The extended region of south polar stratospheric emission has cooled dramatically poleward of the sharp temperature gradient near 75°S (by approximately -5K/yr), coinciding with a depletion in the abundances of acetylene (0.030±0.005ppm/yr) and ethane (0.35±0.1ppm/yr), and suggestive of stratospheric upwelling with vertical wind speeds of w≈+0.1mm/s. The upwelling appears most intense within 5° latitude of the south pole. This is mirrored by a general warming of the northern polar stratosphere (+5K/yr) and an enhancement in acetylene (0.030±0.003ppm/yr) and ethane (0.45±0.1ppm/yr) abundances that appears to be most intense poleward of 75°N, suggesting subsidence atw≈-0.15mm/s. However, the sharp gradient in stratospheric emission expected to form near 75°N by northern summer solstice (2017, Ls=90°) has not yet been observed, so we continue to await the development of a northern summer stratospheric vortex. The peak stratospheric warming in the north occurs at lower pressure levels (p<1mbar) than the peak stratospheric cooling in the south (p>1mbar). Vertical motions are derived from both the temperature field (using the measured rates of temperature change and the deviations from the expectations of radiative equilibrium models) and hydrocarbon distributions (solving the continuity equation). Vertical velocities tend towards zero in the upper troposphere where seasonal temperature contrasts are smaller, except within the tropospheric polar cyclones where w≈±0.02mm/s. North polar minima in tropospheric and stratospheric temperatures were detected in 2008-2010 (lagging one season, or 6-8years, behind winter solstice); south polar maxima appear to have occurred before the start of the Cassini observations (1-2years after summer solstice), consistent with the expectations of radiative climate models. The influence of dynamics implies that the coldest winter temperatures occur in the 75-80° region in the stratosphere, and in the cool polar zones in the troposphere, rather than at the poles themselves. In addition to vertical motions, we propose that the UV-absorbent polar stratospheric aerosols entrained within Saturn's vortices contribute significantly to the radiative budget at the poles, adding to the localised enhancement in the south polar cooling and north polar warming poleward of ±75°.